MAKING APPLICATION DESIGN DIAGRAM plot (flowchart) - Hariyanto Hariyanto (JAKSTIK Journal, 2005)
As technology advances and information age, the programming language progress veryrapidly, both in usage and in making program.Programming languages and algorithms necessary if a problem should be solved throughcomputer technology, in order to save time and simplify their use.In general, before a problem solved through a programming language, first the problem wassolved through a flowchart diagram, the tool graphically depiction of the steps and thesequence of procedures of a program. Flowchart to help analysts and programmers to solvethe problem into segments that are smaller and help in analyzing alternatives in the operation.Flowchart usually facilitate the settlement of a problem, especially problems that need to befurther studied and evaluated.